2021
DOI: 10.1093/jas/skab327
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of tissue dimensions and three captive bolt placements on cadaver heads from mature swine (Sus scrofa domesticus) > 200 kg body weight

Abstract: Three penetrating captive bolt (PCB) placements were tested on cadaver heads from swine with estimated body weight (BW) >200 kg (sows = 232.9 ± 4.1 kg; boars = 229.3 ± 2.6 kg). The objectives were to determine tissue depth, cross-sectional brain area, visible brain damage (BD), regions of BD, and bolt-brain contact; and determine relationships between external head dimensions and tissue depth at each placement. A Jarvis PAS – Type P 0.25R PCB with a Long Stunning Rod Nosepiece Assembly and 3.5 gr power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…The majority of peer-reviewed scientific publications on the topic at the time of this review were focused on NPCB euthanasia of neonatal (3 d of age or younger) pigs ( Casey-Trott et al, 2013 , 2014 ; Grist et al, 2017 , 2018a , 2018b ). At the time of this review, one peer-reviewed scientific publication exists related to the PCB euthanasia of grower-finisher swine ( Anderson et al, 2019 ) and two on the PCB euthanasia of breeding swine ( Anderson et al, 2021 ; Kramer et al, 2021 ). In addition, a thesis focuses on the NPCB and PCB euthanasia of six weight classes of swine, from 2 to 200 + kg ( Woods, 2012 ).…”
Section: Swinementioning
confidence: 99%
See 4 more Smart Citations
“…The majority of peer-reviewed scientific publications on the topic at the time of this review were focused on NPCB euthanasia of neonatal (3 d of age or younger) pigs ( Casey-Trott et al, 2013 , 2014 ; Grist et al, 2017 , 2018a , 2018b ). At the time of this review, one peer-reviewed scientific publication exists related to the PCB euthanasia of grower-finisher swine ( Anderson et al, 2019 ) and two on the PCB euthanasia of breeding swine ( Anderson et al, 2021 ; Kramer et al, 2021 ). In addition, a thesis focuses on the NPCB and PCB euthanasia of six weight classes of swine, from 2 to 200 + kg ( Woods, 2012 ).…”
Section: Swinementioning
confidence: 99%
“… Anderson et al (2021) evaluated tissue depth measurements, brain area, brain contact plane, and brain damage associated with the frontal, temporal, and behind ear PCB placements on cadaver heads from mature sows and boars (BW > 200 kg). The authors concluded that the frontal placement appeared to be the most reliable with the PCB device used due to the least total tissue thickness, greatest potential target area, and high prevalence of brain damage.…”
Section: Swinementioning
confidence: 99%
See 3 more Smart Citations